Algorithms for information retrieval - Kwok, Jee Ann. (2008)
The main focus of this dissertation is in its testing and evaluation of five string matching algorithms. All the selected algorithms were coded in C programs, and then a few test cases were also developed to test the efficiencies of the above algorithms under different simulations. From the results, the dissertation concludes that there is a variation of performance in terms of execution time as well as number of comparisons made for different algorithms when subjected under different testing conditions. In terms of execution time, the Horspool algorithm has achieved the best performance. The Boyer- Moore algorithm is more efficient in terms of direct character comparisons.